IMPLEMENTASI PERANCANGAN APLIKASI SISTEM INFORMASI RESERVASI KAMAR PADA SISTEM PERHOTELAN - Andriansyah, M. Juli; Hidayat, M. Ihsan; Lumbanbatu, Katen; Ambarita, Indah (STMIK Kaputama, 2018)
In the management of a hotel, there is a room reservation process to run slowly, it requires a lot of recording resulted in a process running slow, inefficient, and prone to error (human error). The process of checking the room status manually dna statements also require energy and time. Therefore, it can be built a room reservation information system applications. In the system, do the reservation process, check-in and check-out room. In the process of the reservation, the room number will be blocked in the reservation process, so as to avoid double booking the same room and the same date. Then at the time of check-in, room status will change to fill up, and when you check-out, room status is changed back into blank. Application can be used to make the reservation process, the process of check-in and check-out process at the hotel. Applications provides reports reservation, check-in, check-out and statements of earnings, so the report printing can be done quickly and avoid mistakes (human error) when preparing the report done manually.